Cloud Computing and Financial Reporting Quality: The Moderating Effect of Corporate Governance - Okon, Edet E; Nwaobia, Appolos N.; Ajibade, Ayodeji T. (Archives of Business Research, 2025)
The rapid advancement of cloud computing has transformed financial reporting practices, offering opportunities for enhanced data accessibility, accuracy, and efficiency. However, its adoption also introduced challenges relating to cybersecurity, regulatory compliance, and financial data integrity. Thus, the study examined the interplay between cloud computing and financial reporting quality, with corporate governance as a moderating factor in Nigerian consumer goods companies. The research employed a descriptive survey design, and collected primary data from 394 staff across 21 listed consumer goods firms. Using regression analysis, the study evaluated how cloud computing (applications, platforms, and infrastructures) influence financial reporting quality and how governance structures (board quality, audit committee effectiveness, and control environment) moderate these effects. The result revealed that cloud computing had substantial impact on the quality of financial reporting (Adj.R2 = 0.30, F(2, 391) = 169.73, p < 0.05) of consumer goods firms in Nigeria. Also, corporate governance moderated the effect of cloud computing on financial reporting quality (∆R2 = 0.14, ∆F(2, 391) = 48.51, p < 0.05) of consumer goods firms. This implies that corporate governance significantly enhances financial reporting quality in a cloud computing environment by mitigating risks associated with data security and compliance. Additionally, strong corporate governance structures improve transparency, stakeholder confidence, and regulatory adherence. The study recommends a strengthened corporate governance structures, including independent audit committees and technology-competent boards, to maximize the benefits of cloud computing while ensuring financial reporting quality